2022
DOI: 10.1029/2021sw002907
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting GICs and Geoelectric Fields From Solar Wind Data Using LSTMs: Application in Austria

Abstract: The forecasting of local GIC effects has largely relied on the forecasting of dB/dt as a proxy and, to date, little attention has been paid to directly forecasting the geoelectric field or GICs themselves. We approach this problem with machine learning tools, specifically recurrent neural networks or LSTMs by taking solar wind observations as input and training the models to predict two different kinds of output: first, the geoelectric field components Ex and Ey; and second, the GICs in specific substations in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 76 publications
1
10
0
Order By: Relevance
“…GIC values during the geomagnetic storms are usually in the order of tens of amperes (e.g., Švanda et al., 2021; Torta et al., 2021) and our results confirms these observation (we do not observe values higher than 100 A). Moreover, GICs computations correspond to values mentioned for mid‐latitudes by (e.g., Albert et al., 2022; Bailey et al., 2022). For comparison, for Simpevarp‐2 power substation on 6 April 2000, Wik et al.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…GIC values during the geomagnetic storms are usually in the order of tens of amperes (e.g., Švanda et al., 2021; Torta et al., 2021) and our results confirms these observation (we do not observe values higher than 100 A). Moreover, GICs computations correspond to values mentioned for mid‐latitudes by (e.g., Albert et al., 2022; Bailey et al., 2022). For comparison, for Simpevarp‐2 power substation on 6 April 2000, Wik et al.…”
Section: Resultssupporting
confidence: 82%
“…It would be interesting to apply GEDMap in this context. Moreover, the GIC problems at middle-and low-latitude transmission lines have increasingly gained attention (e.g., Albert et al, 2022;Bailey et al, 2022;Barbosa et al, 2015;Švanda et al, 2021;Torta et al, 2012;Tozzi et al, 2019;Zois, 2013). In the light of this task proposed procedure of the geoelectric field mapping, not based on SECS methods (appropriate for high latitudes) can be tested and applied.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, with the recent storms we now have sufficient data to reliably calculate the GICs in the Austrian power grid, which is unfortunately low for studying larger GIC events, however due to the relaxation of maximum measurement limits in the past year, we now have sufficient data to estimate GIC levels from recent storms. A historical analysis has been carried out in another recent study (Bailey et al., 2022), giving an estimate for the largest GICs during the 2003 Halloween storm that likely ranged from at least 30 A up to 60 A.…”
Section: Discussionmentioning
confidence: 99%
“…Our choice of threshold for spike detection (100 nT/min) can be motivated by previous investigations, for example, by a recent study of the power grid in Sweden, where a horizontal component dB / dt down to 30 nT/min can cause detectable GICs, reminiscent of grounding faults, and 200–500 nT/min can cause a temporary loss of individual transformers (Rosenqvist et al., 2022). In another recent study relating dB/dt variations to GICs in Austrian infrastructure, it was found that dB / dt of the order of 100 nT/min can be associated with cumulative GICs (over an hour at selected transformer stations) larger than 200 Ah (Bailey et al., 2022). Weygand (2021) listed dB / dt for three well‐studied previous geomagnetic storms, and found that peak dB / dt values of ∼60 nT/min can correspond to GIC magnitudes up to 40 A.…”
Section: Instrumentation Data and Methodsmentioning
confidence: 99%